The Impact of Motivation Towards Employee Performance in Finance Department at Jw Marriott, Medan - Gasiella, Gasiella; Kelana, Jimmy; Mega Hernawati Harefa (Lembaga Pengembangan Kinerja Dosen, 2024)
In managing the hospitality industry, one of the goals is to increase the performance of its employees/ human resources. Employee performance has an important role in the overall performance and growth of the company. To perform well, employees must have motivation. Work motivation sparks a sense of purpose and passion in employees, encouraging them to invest time and energy in their work efforts. This study aims to determine whether there is an impact of motivation towards employee performance in finance department at JW Marriott, Medan.In this study, indicator of motivation are achievement, recognition and responsibility. Indicator of employee performance are work quality, work quantity and work behavior.The data analysis method in this study is the descriptive analysis method, validity test, reliability test, descriptive statistics, normality test, coefficient of correlation test, coefficient of determination test, linear regression analysis, and hypothesis test. Sampling in this study is a census sampling method with sample size is 32 employees.he result of the coefficient of correlation is 0.717. The result of the coefficient of determination is 51.5%. The regression equation is Y = 5.024 + 0.674X. The result of the Z test shows that the Z count > Z table (3.99 > 1.96). The results of descriptive statistics show that the average employee is disagrees that there is positive motivation and employee performance in the hotel. The conclusion of this study means that motivation has impact towards employee performance in finance department at JW Marriott, Medan.